Perspektif Sikap Kewirausahaan Peserta Didik Melalui Pembelajaran IPA Berbasis Potensi Lokal Reyog Ponorogo - Gagan Ganiya Aulia Rahman; Gus Rijal Mujahidin; Sofyan Dwi Nugroho; Insih Wilujeng; Sri Rejeki Dwi Astuti; Suyanta Suyanta (Jurnal Penelitian Pendidikan IPA, 2023)
Science learning that is oriented towards entrepreneurship has not been able to produce students who have an entrepreneurial attitude. This study aims to identify the effect of local potential-based science learning in Reyog Ponorogo, the Dhadak Merak dance on the entrepreneurial attitude perspective of junior high school students. The research method used is quantitative descriptive with a one-group pretest-posttest design at SMP Negeri 3 Depok Sleman. The sample used was 20 students who were selected using the cluster random sampling technique. Entrepreneurial attitude perspective data collection was carried out using an entrepreneurial attitude questionnaire. Data analysis used paired sample t-test. Based on the results of the study, the paired sample t-test sig (2-tailed) was 0.000, so there are differences in pretest and posttest. It can be concluded that science learning based on local potential in Reyog Ponorogo has an effect on the entrepreneurial perspective of junior high school students.